Автоматизація створення задач в Atlassian JIRA за допомогою Camunda для оптимізації роботи QA - Харченко, В. В. (ХНУРЕ, 2024)
Camunda and are integral tools for streamlining business processes and project management, respectively. My software application combines the workflow automation capabilities of Camunda with the project management features of Atlassian Jira to enhance the efficiency of QA engineers. By automating tasks and synchronizing workflows, it provides a centralized platform for QA management within the familiar Jira environment. With intuitive dashboards and monitoring tools that provides Camunda Cockpit, the application offers real-time insights to optimize QA operations.
Keywords: QA; Atlassian JIRA; Camunda